UTILIZING INTEGRATION OF SOME REMOTELY SENSED MORPHOMETRIC ASPECTS AND HYPSOMETRIC ANALYSES TO DETERMINE THE GEOMORPHOLOGICAL CHARACTERSTICS OF AL-ABEADH VALLEY WATERSHED - A. Jawad, L. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The precise extracting, studying, and interpretation of watershed morphometric database is the constitutional adobe for watershed accurate geomorphological comprehension building. In this work a new approach was adopted by utilizing three different schemes to extract morphometric database, in each scheme the principle of data integration used to define the optimum algorithm for database building; then after extraction; Principle of geographical information intersection applied to form factual geomorphological comprehension for the studied region. In the first scheme according to streams profile it was obvious that geomorphological age decrease with stream order increment (the period generally decrease when oncoming to the watershed sink). The second scheme shows by using some quantitative morphometric parameters that watershed's erosion power is slight and sediments are relatively remain near basin recharche zones (i.e. The basin is generally in youth period of geomorphological spectrum).in third scheme hypsometric analyses (factor and curve) utilized to determine basin geomorphological characteristics. each sub-zone area and age was stated according to hypsometric factor equation. The hypsometric curve clarify that diffusive erosion processes are dominated and less than basin half area was erosion yielding tons of deposit in lower parts of the valley.